Crime and the business cycle in post-war Britain revisited - Hale, Chris (The British journal of criminology, 1998)
The relationships between property crime and the economy are re-examined. The work of Field (1990) and Pyle and Deadman (1994) are reviewed. Whilst both analyses have made substantial contributions to emphasizing the importance of economic factors in determining crime it is argued both have weaknesses. Field ignores the importance of long-run equilibrium relationships whilst errors in the interpretation of Pyle and Deadman lead them to conclude that personal consumption, unemployment and Gross Domestic Product may be used interchangeably. Results are presented which show that personal consumption alone has a long-run equilibrium relationship with property crime. Personal consumption also features in the short-run dynamic models of crime. The long-run effect is interpreted in terms of increased opportunity or availability of targets whilst the short-run result corresponds to a motivational effect. Whilst unemployment has no role in explaining long-run trends in crime it is a factor in explaining short-run fluctuations